Parcerias sexuais de pessoas vivendo com o Vírus da Imunodeficiência Humana - Layze Braz de Oliveira; Matheus Costa Brandão Matos; Giselle Juliana de Jesus; Renata Karina Reis; Elucir Gir; Telma Maria Evangelista de Araújo (Universidade Federal do Ceará, 2017)
Objective: to characterize the sexual partnerships established by people living with the Human Immunodeficiency Virus. Methods: an epidemiological study carried out with 173 participants in a medical assistance service specialized in the treatment of people with Human Immunodeficiency Virus. Data were collected through an individual interview with a specific questionnaire for the study. Pearson's Chi-square test was used to analyze the data. Results: the majority of the participants were male, young adults (54/30.9%), single (94/53.7%), complete high school (72/41.1%) and sexually infected (150/85.7%). The variables gender (p<0.001), marital status (p<0.001), living with partner (p<0.001), exposure form (p=0.040) and partner serology (p<0.001) showed statistical difference. Conclusion: people with this infection establish different forms of sexual partnerships, which were influenced by sex, marital status, living with the partner, form of exposure and serology of the partner.